Research and reasoning of organizational and technological solutions of the regulated systems of the revitalization of construction production processes - Osypova, А. (Ways to Improve Construction Efficiency, 2019)
Determination of the construction-ecological situation (BES). The groups of anthropogenic landscapes, which are accepted for the ideal research models and are presented in a graphical form with a list of specific elements of the environment, which have been destroyed, have been formed. Seven complementary complexes of organizational and technological decisions of the revitalization of construction processes are formed, which are organized according to the significance of protected anthropogenic landscapes.